If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(1 + 6x) = -102 (1 * 6 + 6x * 6) = -102 (6 + 36x) = -102 Solving 6 + 36x = -102 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 36x = -102 + -6 Combine like terms: 6 + -6 = 0 0 + 36x = -102 + -6 36x = -102 + -6 Combine like terms: -102 + -6 = -108 36x = -108 Divide each side by '36'. x = -3 Simplifying x = -3
| -4(u+5)+3u= | | 10d-6=4s-15-3d | | 3(5-4a)=99 | | 6x+5+4x-3=122 | | -92=4(3k-2) | | 8x^2+2x+-15=0 | | z+.625=.9375 | | (x+5)2=108 | | (7+y)(4y+5)=0 | | 20+12x=-128 | | (m^5n^5)^1/6/3(mn)^-1/6 | | 3n=1/81 | | 224=d-12 | | (33*5280)/(60) | | 70=al | | 6r+9=16+7r | | 9x^2-11x-2=0 | | x-5=1/12 | | (16y^3/8y^4)^-4 | | 12+6x=5x+6 | | 2(3x-4)=118 | | (4-1/2c)-1/3[3/4(1-2c)]1/12c | | 2x+5=-4x-6 | | (64m^1/2n÷m^-2n4/3)^1/2 | | 203/x=7 | | x/21=21 | | 4x+6=-2x-6 | | 14y^2-12y+3=0 | | e^2x=-4x | | .30x+6y=200 | | 3.5y-2.5y-6.3=-1.0-2.5 | | 2x+3-8(x+1)=3x+2 |